Preparation method of illite smectite mixed-layer clay-based chlorantraniliprole nano suspending agent
Through high-pressure homogenization treatment and water-based nano-grinding process of Imon mixed clay, the chlorobenzamide nanosuspension agent was prepared, which solved the problems of poor water dispersion and large particle size, and achieved efficient and stable nano-scale dispersion and low Cost production, suitable for industrial applications.
Patent Information
- Application Number
- CN202411424056.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The chloridon benzamide suspension agent has problems of poor water dispersion and large particle size, which affects its stability and efficacy.
Using Imon mixed layer clay as a carrier, the sheet structure is peeled off by high-pressure homogenization technology, combined with modifiers and dispersants, and used water-based nano-grinding technology to prepare chlorobenzamide nanosuspension agent to form high dispersion and stability three-dimensional network structure.
It improves the stability and dispersion of chlorobenzamide suspension agent, reduces production costs, meets the requirements of nano-scale dispersion and heat storage stability, and is suitable for industrial mass production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pesticides and their preparations, and in particular to a method for preparing an illite-montmorillonite mixed-layer clay-based chlorantraniliprole nano suspension, belonging to the technical field of high-value application of clay minerals. Background Art
[0002] Pesticide nanosuspensions eliminate the use of organic solvents, improve the water solubility, dispersibility, permeability and biological activity of the original pesticide, increase the utilization of pesticides, and reduce environmental pollution. They have now become one of the research hotspots in the field of international pesticide formulations.
[0003] Chlorantraniliprole is a new type of diamide insecticide with high efficiency and broad spectrum. Its existing dosage forms mainly include water suspension concentrate (202210316202.1, 202211593908.9, 202310174153.7), water dispersible granules (World Pesticides, 2023, 45(8): 32-35) and granules (202210888755.4). These dosage forms overcome the disadvantage of chlorantraniliprole being poorly soluble in water and improve its bioavailability, but the particle size is relatively large (the national standard stipulates that the average particle size is ≤5μm), which affects the efficacy of the drug.
[0004] Sun Yu et al. used lignin and polycarboxylates with different structures as dispersants by water-based sand milling to prepare chlorantraniliprole nanosuspensions (Industrial Crops&Products 214 (2024) 118539). The D90 particle size of the suspensions was less than 200 nm, and their suspension rate, water separation rate, thermal storage stability, and decomposition rate all met the national standard requirements. However, their suspension stability still needs to be improved.
[0005] Clay minerals are a class of hydrated aluminosilicate minerals with layered or layered chain structures, including kaolinite, montmorillonite, vermiculite, sepiolite, rectorite, halloysite, etc. They have the advantages of large specific surface area and strong adsorption. They can form a unique three-dimensional network structure in aqueous media, increase the viscosity of the system, and provide good storage stability and thixotropy. These characteristics make clay minerals widely used as additives in various industrial fields.
[0006] Illite-montmorillonite mixed-layer clay is an intermediate product of montmorillonite to illite, and has the dual properties of montmorillonite and illite. It can form a stable suspension in an aqueous medium, which helps the uniform dispersion of the material, but the lamellae stacking affects the suspension stability. Therefore, the present invention is directed to the problems existing in the current chlorantraniliprole suspension, utilizes a high-pressure homogenization technology to peel off the lamella structure of the illite-montmorillonite mixed-layer clay, improves its dispersibility, and then by screening a high-efficiency modifier and a dispersant, adopts a water-based nano-grinding process to prepare a nano suspension, and develops a green and environmentally friendly nano pesticide preparation. Summary of the invention
[0007] Aiming at the problems of poor water dispersibility and large particle size of chlorantraniliprole suspension, the present invention uses illite mixed-layer clay as a carrier, adopts high-pressure homogenization technology and water-based nano-grinding process under the synergistic effect of a modifier and a dispersant to prepare a chlorantraniliprole nano suspension.
[0008] In order to achieve the above object, the present invention provides a method for preparing a chlorantraniliprole nano water suspension concentrate based on illite and montmorillonite mixed-layer clay, comprising the following steps: (1) High-pressure homogenization treatment of illite-montmorillonite mixed-layer clay: The illite-montmorillonite mixed-layer clay ore is crushed, ground, and sieved to remove quartz sand impurities to obtain purified illite-montmorillonite mixed-layer clay. The purified illite-montmorillonite mixed-layer clay is then dispersed in water, stirred and hydrated for 4 to 6 hours, and then filtered through a 400-600 mesh sieve to further remove quartz sand. Subsequently, a high-pressure homogenization and peeling treatment is performed to obtain a purified nano-sized illite-montmorillonite mixed-layer clay slurry. When the purified illite montmorillonite mixed layer clay is dispersed in water, the solid-liquid ratio of the purified illite montmorillonite mixed layer clay and water is 1:20 (g / mL), and the sand content of the illite montmorillonite mixed layer clay slurry is ≤1%. The homogenization pressure of the high-pressure homogenization peeling treatment is 5MPa to 70MPa.
[0009] (2) Preparation of nanosuspension: Add modifier, chlorfenapyr and dispersant to the purified nano-sized illite / montmorillonite mixed-layer clay slurry in sequence, stir to form a uniform suspension, and then ball mill at 100-800 rpm for 30-240 min to obtain illite / montmorillonite mixed-layer clay-based chlorfenapyr nanosuspension.
[0010] The mass of the purified illite-montmorillonite mixed-layer clay is 0.5% to 20% of the mass of chlorantraniliprole. The modifier is at least one of alkyl trimethyl quaternary ammonium salt, alkyl aryl sulfonate, and alkyl sulfate, and the amount of the modifier added is 0.5% to 3.0% of the mass of chlorantraniliprole. The dispersant is at least one of carboxymethyl cellulose, carboxymethyl chitosan, N-succinyl chitosan, modified bamboo fiber, and lignin sulfonate, and the amount of the dispersant added is 2% to 10% of the mass of chlorantraniliprole. During the ball milling process, the ball-to-material ratio is 10:1 to 50:1, and the grinding ball particle size is 2 mm.
[0011] Figure 1 TEM images of illite-montmorillonite mixed-layer clay before and after exfoliation (a, b). Figure 1 As shown, the layers of the raw ore of I-Smectite mixed layer clay are in a stacked state ( Figure 1 a), After homogenization, the morphology of the layer appears as a single flake, and the size of the flake is reduced ( Figure 1b) This indicates that the strong cavitation, shearing and collision effects during the high-pressure homogenization process cause a large number of flakes in the illite mixed layer clay to be collectively peeled off into single flakes or small-diameter flakes, and the flake dispersion is significantly improved, so that the illite mixed layer clay has a larger specific surface area, and its surface or end face exposes more negative charges. The irregular arrangement of a large number of highly dispersed flakes is conducive to improving the suspension performance of the illite mixed layer clay, and ultimately achieving the high efficiency and stability of the chlorantraniliprole nanosuspension.
[0012] Figure 2 The infrared spectra of chlorantraniliprole (a), the nanosuspension obtained in Example 1-2 of the present invention (b, c) and the illite-montmorillonite mixed layer clay (d). Figure 2 a and Figure 1 Compared with d Figure 2 In b and c, the region at 3623 cm -1 、1637 cm -1 and 1032 cm -1 The peaks at 3000-2800 cm-1 are respectively attributed to the stretching vibration of A1-OH in the 2:1 unit layer of montmorillonite, the bending vibration of the HOH bond of water molecules, and the asymmetric stretching vibration peaks of the Si-O-Si bond connecting two inverted SiO4 tetrahedra. -1 、1662~1640 cm -1 and 1577~1305 cm -1 The above absorption peaks are attributed to the characteristic absorption bands of organic functional groups such as -CH2, C=C, and CN on the chlorantraniliprole molecule. Except for the change in intensity, there is no obvious shift in the above absorption peaks, which indicates that chlorantraniliprole does not react chemically with other substances.
[0013] Figure 3 The thermogravimetric analysis curves of the samples of chlorantraniliprole and the nanosuspension obtained in Example 1 after being dried at 105°C. Figure 3 It can be seen that the weight loss of chlorantraniliprole in the range of room temperature to 100℃ is mainly attributed to the removal of surface adsorbed water, and the weight loss in the temperature range of 276~350℃ is mainly attributed to the decomposition of organic matter, and the weight loss rate in this range is more than 90%. After the introduction of the illite-montmorillonite mixed layer clay, the final weight loss rate of the dry sample of the suspension was less than 80%. This is because the illite-montmorillonite mixed layer clay acts as a thermal barrier, making it difficult for the small molecules generated by thermal decomposition to diffuse and volatilize, thereby enhancing the thermal stability of the chlorantraniliprole suspension.
[0014] Figure 4The digital photos of the dispersion stability of the nanosuspension obtained in Example 1 (a) and Example 2 (b) of the present invention before and after sealed storage at 60°C for 15 days are shown. After sealed storage at 60°C for 15 days, no precipitation, water separation, separation and stratification occurred, and the mass change of the sample before and after hot storage was less than 1.0%, which shows that the suspension has good hot storage stability and meets the requirements of the national standard GB / T19136-2021.
[0015] Figure 5 The particle size distribution of the nanosuspension obtained in Example 1 after sealed storage at 60°C for 15 days and after dilution 200 times is given. Figure 5 It can be seen that the particle size distribution of the suspension concentrate shifted to the right after hot storage, that is, the particle size of the suspension concentrate increased, but was still less than 300 nm. This indicates that the suspension concentrate particles agglomerated during storage.
[0016] In summary, the present invention has the following advantages compared with the prior art: 1. The present invention uses highly dispersed Imonite mixed-layer clay after flaking as a carrier of chlorantraniliprole suspension, and the formed three-dimensional network structure can improve the suspension stability of chlorantraniliprole. At the same time, the nanosheets can also assist the dispersant to further prevent the agglomeration of chlorantraniliprole molecules, so that the suspension can reach nano-scale dispersion.
[0017] 2. Imonite mixed-layer clay is widely available and inexpensive. The addition of Imonite mixed-layer clay can reduce the use of dispersants and polymer stabilizers, thereby reducing the production cost of chlorfenapyr suspension. The entire preparation process is easy to control and is green and environmentally friendly, making it easy to achieve industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 TEM images of the illite-montmorillonite mixed-layer clay before (a) and after (b) exfoliation. Figure 2 The infrared spectra of chlorantraniliprole (a), the nanosuspension prepared in Example 1-2 of the present invention (b, c) and illite-montmorillonite mixed-layer clay (d); Figure 3 Thermogravimetric analysis curves of chlorantraniliprole and the nanosuspension prepared in Example 1 after being dried at 105°C; Figure 4 The digital photos of the dispersion stability of the nanosuspension obtained in Example 1 (a) and Example 2 (b) of the present invention before and after heat storage; Figure 5 The particle size distribution of the nanosuspension obtained in Example 1 before and after heat storage. DETAILED DESCRIPTION
[0019] The preparation method of the illite mixed-layer clay-based chlorantraniliprole nanosuspension of the present invention is further described below through specific examples.
[0020] Example 1 (1) 50 g of natural illite-montmorillonite mixed-layer clay ore was crushed and ground, and then passed through 300 mesh to obtain purified illite-montmorillonite mixed-layer clay. It was then evenly dispersed in 1000 mL of water, stirred for 4 h, and then passed through 400 mesh. It was then subjected to 10 MPa high-pressure homogenization to obtain a highly dispersed illite-montmorillonite mixed-layer clay slurry after exfoliation, with a sand content of 0.68%; (2) To a slurry containing 0.60 g of purified illite mixed-layer clay, 0.09 g of sodium dodecylbenzene sulfonate, 3.00 g of chlorantraniliprole and 0.09 g of carboxymethyl cellulose were added in sequence and stirred for 120 min to form a uniform suspension. The mixture was then ball milled at a ball-to-material ratio of 20:1 and a rotation speed of 600 rpm for 60 min to obtain an illite mixed-layer clay-based chlorantraniliprole nanosuspension with an average particle size of 21.81 nm.
[0021] Example 2 (1) 50 g of natural illite-montmorillonite mixed-layer clay ore was crushed and ground, then passed through 300 mesh, and then evenly dispersed in 1000 mL of water. After continuous stirring for 4 h, the slurry was passed through 600 mesh, and then subjected to 70 MPa high-pressure homogenization to obtain a highly dispersed illite-montmorillonite mixed-layer clay slurry after exfoliation, with a sand content of 0.52%; (2) 0.03 g of sodium dodecylbenzene sulfonate, 3.00 g of chlorantraniliprole and 0.06 g of carboxylated bamboo fiber were added to a slurry containing 0.15 g of purified illite mixed-layer clay in sequence and stirred for 60 min to form a uniform suspension. The mixture was then ground at a ball-to-material ratio of 10:1 and a rotation speed of 400 rpm for 30 min to obtain an illite mixed-layer clay-based chlorantraniliprole nanosuspension concentrate with an average particle size of 113.17 nm.
[0022] Example 3 (1) 50 g of natural illite-montmorillonite mixed-layer clay ore was crushed and ground, then passed through 400 mesh, and then evenly dispersed in 1000 mL of water. After continuous stirring for 4 h, the slurry was passed through 600 mesh, and then subjected to 50 MPa high-pressure homogenization to obtain a highly dispersed illite-montmorillonite mixed-layer slurry after layer exfoliation, with a sand content of 0.46%; (2) 0.09 g octadecyltrimethylammonium chloride, 3.00 g chlorantraniliprole, 0.06 g sodium lignin sulfonate and 0.03 g carboxylated bamboo fiber were added to a slurry containing 0.30 g purified illite mixed-layer clay in sequence and stirred for 120 min to form a uniform suspension. The mixture was then ball milled at a ball-to-material ratio of 30:1 and a rotation speed of 600 rpm for 60 min to obtain an illite mixed-layer clay-based chlorantraniliprole nanosuspension concentrate with an average particle size of 129.27 nm.
[0023] Example 4 (1) 50 g of natural illite-montmorillonite mixed-layer clay ore was crushed and ground, then passed through 300 mesh, and then evenly dispersed in 1000 mL of water. After continuous stirring for 4 h, the slurry was passed through 600 mesh, and then subjected to 30 MPa high-pressure homogenization to obtain a highly dispersed illite-montmorillonite mixed-layer clay slurry after exfoliation, with a sand content of 0.47%; (2) 0.09 g sodium dodecyl sulfate, 3.00 g chlorantraniliprole and 0.06 g of N -succinyl chitosan, stirred for 120 min to form a uniform suspension, and then ball milled for 60 min at a ball-to-material ratio of 50:1 and a rotation speed of 600 rpm to obtain an immonite mixed-layer clay-based chlorantraniliprole nanosuspension with an average particle size of 83.97 nm.
[0024] Example 5 (1) 50 g of natural illite-montmorillonite mixed-layer clay ore was crushed and ground, then passed through 400 mesh and evenly dispersed in 1000 mL of water. After continuous stirring for 4 h, the slurry was passed through 600 mesh and then subjected to 5 MPa high-pressure homogenization to obtain a highly dispersed illite-montmorillonite mixed-layer clay slurry after exfoliation, with a sand content of 0.46%; (2) To a slurry containing 0.20 g of purified illite mixed-layer clay, 0.06 g of dodecyltrimethylammonium chloride, 3.00 g of chlorantraniliprole and 0.03 g of sodium lignin sulfonate were added in sequence and stirred for 120 min to form a uniform suspension. The mixture was then ball milled at a ball-to-material ratio of 50:1 and a rotation speed of 600 rpm for 60 min to obtain an illite mixed-layer clay-based chlorantraniliprole nanosuspension concentrate with an average particle size of 180.3 nm.
Claims
1. A method for preparing a chlorfenapyr nanosuspension concentrate based on an Ionite mixed-layer clay, comprising the following steps: (1) High-pressure homogenization treatment of illite-montmorillonite mixed-layer clay: The illite-montmorillonite mixed-layer clay ore is crushed, ground, and sieved to remove quartz sand impurities to obtain purified illite-montmorillonite mixed-layer clay. The purified illite-montmorillonite mixed-layer clay is then dispersed in water, stirred and hydrated for 4 to 6 hours, and then filtered through a 400-600 mesh sieve to further remove quartz sand. Subsequently, a high-pressure homogenization and peeling treatment is performed to obtain a purified nano-sized illite-montmorillonite mixed-layer clay slurry. (2) Preparation of nanosuspension: Add modifier, chlorfenapyr and dispersant to the purified nano-sized illite / montmorillonite mixed-layer clay slurry in sequence, stir to form a uniform suspension, and then ball mill at 100-800 rpm for 30-240 min to obtain illite / montmorillonite mixed-layer clay-based chlorfenapyr nanosuspension.
2. The method for preparing a chlorfenapyr nanosuspension concentrate based on an Ionite mixed-layer clay as claimed in claim 1, characterized in that: In step (1), when the purified illite montmorillonite mixed layer clay is dispersed in water, the solid-liquid ratio of the purified illite montmorillonite mixed layer clay and water is 1:20, and the sand content of the illite montmorillonite mixed layer clay slurry is ≤1%.
3. The method for preparing a chlorfenapyr nanosuspension concentrate based on an Ionite mixed-layer clay as claimed in claim 1, characterized in that: In step (1), the homogenization pressure of the high-pressure homogenization flaking process is 5 MPa to 70 MPa.
4. The method for preparing a chlorfenapyr nanosuspension concentrate based on an Ionite mixed-layer clay as claimed in claim 1, characterized in that: In step (2), the mass of the purified illite-montmorillonite mixed-layer clay is 0.5% to 20% of the mass of chlorantraniliprole.
5. The method for preparing a chlorfenapyr nanosuspension concentrate based on Imonite mixed-layer clay as claimed in claim 1, characterized in that: In step (2), the modifier is at least one of alkyl trimethyl ammonium salt, alkyl aryl sulfonate and alkyl sulfate, and the amount of the modifier added is 0.5% to 3.0% of the mass of chlorantraniliprole.
6. The method for preparing a chlorfenapyr nanosuspension concentrate based on Imonite mixed-layer clay as claimed in claim 1, characterized in that: In step (2), the dispersant is at least one of carboxymethyl cellulose, carboxymethyl chitosan, N-succinyl chitosan, modified bamboo fiber, and lignin sulfonate, and the amount of the dispersant added is 2% to 10% of the mass of chlorfenapyr.
7. The method for preparing a chlorfenapyr nanosuspension concentrate based on Imonite mixed-layer clay as claimed in claim 1, characterized in that: In step (2), the ball-to-material ratio during the ball milling process is 10:1-50:1, and the grinding ball particle size is 2 mm.
Citation Information
Cited By
Method for preparing hectorite-based chlorantraniliprole nano suspending agent based on high-pressure microjet homogenization technology
CN122004205A
